Extracorporeal Membrane Oxygenation Complicated by an Interrupted Inferior Vena Cava. Issue 9 (17th March 2021) - Johnson, Aric J.; Srour, Habib
Abstract : Heterotaxy refers to a congenital disorder in which there is a disruption of the normal left-right axis, resulting in duplication of one laterality, and can affect all of the thoracic and abdominal organs. Findings include atrial isomerism, vascular abnormalities affecting the great vessels, ciliary dyskinesia, polysplenia or asplenia, biliary atresia, and gut malrotation. These anomalies can present unique challenges in the critical care setting, particularly in those requiring mechanical circulatory support. Here, we present a patient with acute respiratory distress syndrome requiring venovenous extracorporeal oxygenation which was complicated by a persistent impedance of flow. She was subsequently discovered to have an interrupted inferior vena cava, where lower limb venous drainage returned to the heart via the azygos and hemiazygos systems. We use this case to also highlight other manifestations of heterotaxy which may affect critical care.